STRENGTHENING HALAL TOURISM DEVELOPMENT IN RIAU PROVINCE IN INDONESIA (International Journal of Islamic Business, 2020)
This study explore and analyze the problems of halal tourism’s development in Riau Province with an Analytic Network Process (ANP) approach. The method used is the Analytic Network Process (ANP) which is a qualitative and quantitative method approach. The type of data that will be used in this research is the primary data and the form of the subject (self-report data). The samples used as respondents in this study were those who were considered experts in the field of halal tourism, namely the government in this case the ministry of tourism, tourism practitioners, regulators or perpetrators industrial activist in the field of tourism, Halal Product Guarantee Agency business and academics took by purposive sampling. The variables of this research are regulation, literacy, human resources, infrastructure, government policies, certification, government commitment, and socio-culture. The findings shows that the internal problems faced in the development of Halal tourism in Riau province based on the order of priority were infrastructure problems, regulatory issues, human resource problems, and literacy problems. Other findings indicate that the external problems faced are based on priority order, including government commitment issues, government policy issues, certification issues, and socio-cultural problems. The Managerial implications for halal tourism stakeholders in Riau province, especially the local government to pay attention to issues of infrastructure development, particularly access to places of halal tourism and have a strong commitment in developing halal tourism in the province.